THE CURRENT SITUATION OF REFUSAL TO PAY HEALTH INSURANCE MEDICAL EXAMINATION AND TREATMENT COSTS AT 19-8 HOSPITAL 2023-2024 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the situation of refusal to pay medical examination and treatment costs covered by health insurance by the Hanoi Social Security agency at 19-8 Hospital for the period 2023–2024.Research method: Retrospective description of secondary data from summary reports, minutes of payment and settlement of health insurance medical examination and treatment costs at the 19-8 Hospital in 2023, 2024.Results and recommendations: The total costs of medical examination and treatment covered by health insurance at 19-8 Hospital reached 373.34 billion VND in 2023 and 401.95 billion VND in 2024. The refusal rate of health insurance payments was 2.16% in 2023 (equivalent to 7.23 billion VND) and 1.2% in 2024 (equivalent to 4.39 billion VND). In 2023, the group with the highest rate of refused payments was Diagnostic Imaging, Functional Exploration (48.64%), while the group with the lowest rate was Drugs, Chemicals, Blood and Blood Products (3.06%). In 2024, Surgeries and Procedures had the highest refusal rate (34.6%), and Drugs, Chemicals, Blood and Blood Products continued to have the lowest (7.2%). We recommend that 19-8 Hospital should make better use of information technology systems to provide alerts, reminders, and early prevention of potential errors, thereby minimizing health insurance costs that may be refused by the Social Security agency.
Keywords: Health insurance; Refusal of payment; Medical examination and treatment costs.